Controls on composition and diagenesis of wave- and river-dominated deltas: impacts on reservoir properties. An example from the La Anita Formation (Argentina). (April 2022) - Moyano-Paz, Damián; Gómez-Dacal, Alejandro R.; Varela, Augusto N.; Comerio, Marcos; Muñoz-Olivero, Tobías M.; Bucher, Joaquín; Richiano, Sebastián; Poiré, Daniel G.
Abstract: Wave-, tidal-, and fluvial-dominated deltas are important hydrocarbon reservoirs worldwide, and it is well known that depositional facies types, detrital composition and diagenetic products are key aspects when evaluating potential reservoir properties. Moreover, detrital composition and diagenetic products are controlled by external forces such as tectonism, climate, and depositional conditions. The Upper Cretaceous La Anita Formation (Austral-Magallanes Basin, Argentina) is a deltaic succession that shows a clear vertical variation in the relative role of wave, tidal and fluvial processes. The formation was accumulated during the foreland stage of the basin under relatively warm climate conditions. A detailed compositional and diagenetic analysis for these deposits is provided to evaluate the role of the controlling factors on the detrital and authigenic composition, and the impact on reservoir properties. Samples were analyzed by conventional petrography, X-ray diffraction and scanning electron microscopy to obtain a full spectrum of its detrital, authigenic and diagenetic composition. The analyzed sandstones were classified as lithic arenites which come from the fold-thrust belt region and from the magmatic arc located toward the westward. The clay mineral composition is characterized by variable proportions of illite, smectite, kaolinite and mixed-layer illite-smectite with the sporadic presence of chlorite. Stratigraphic variations in the abundance of authigenic kaolinite and smectite indicate a change in the climatic conditions during the depositions of the unit evolving from tropical to more temperate conditions. Diagenetic processes affecting the porosity are considered as controlled mainly by the lithological nature of the deposits and depositional facies type. Sandstone porosity is mainly primary in origin, moderate to good in abundance and show micropore to mesopore as the main pore-sizes. This work enhances that the diagenetic products are heavily controlled by the dominant depositional process. The presence of diagenetic products as quartz overgrowth and calcite and hematite cement reduces pore spaces and affects the reservoir properties. The development of these types of cement is conditioned by the relative dominance of wave and river processes. Under wave-dominated conditions, quartz tends to develop thick overgrowths. Conversely, under river-dominated conditions quartz overgrowths are thinner and calcite and hematite cementation patches are developed. Highlights: Compositional and diagenetic analysis for wave- and river-dominated deltaic deposits are performed. Sandstone provenance indicates supply mainly from the uplifted fold-thrust belt and magmatic arc. Vertical variations in clay mineral composition indicate a change in paleoclimatic conditions. The diagenetic processes recorded in the La Anita Formation conditioned the reservoir properties. The development of different diagenetic products is controlled mainly by the dominance of the depositional processes.